(untitled) (Revista Electrónica Calidad en la Educación Superior, 2021)
This work present the requirement of companies in the Pérez Zeledón area in Costa Rica in relation to the proffesional profile of the graduate of Administración de Oficinas career. The type of research used was mixed. The information was obtained by open interviews and focus groups that allowed the population to express their feelings and emotions. The results indicate that there is a high grade of adjust of the graduate profile of the degree to the characteristics required by companies for administrative positions. It´s concluded that the students meets the requirements request by companies and has the technical domain to confront job challenges.